Spatio-temporal profile of innate inflammatory cells and mediators during influenza virus infection (2020)
Influenza virus is a global health concern that causes from mild to severe respiratory disease. A definitive treatment against this pathogen remains elusive, despite significant progress has been made in understanding the host-pathogen interactions that contribute to the progression of the infection. The initial antiviral response against influenza involves the secretion of cytokines and chemokines by immune and non-immune cells. However, the inflammatory process has a double side in the outcome of the infection. On the one hand, inflammation induces the recruitment of different innate and adaptive immune cells to the site of infection, which contributes to the control of the viral dissemination. On the other hand, the excessive production of pro-inflammatory cytokines induces the so-called “cytokine storm” that is characterized by excessive tissue damage, which ultimately leads to organ failure. Recently, different studies have described the early immune response in the upper respiratory tract and the trachea following influenza infection and have identified novel cell mediators, such as inflammatory dendritic cells and γδ T cells, involved in viral recognition and pathogen eradication. This review discusses the function of these early-recruited immune cells and the inflammatory mediators released upon infection. A complete characterization of the role of these new players in the early immune response against influenza might suggest potential targets for therapeutic intervention.